NCOG-46. PERSONALIZED, PARCEL-GUIDED RTMS FOR NEURO-REHABILITATION AFTER TUMOR NEUROSURGERY: SAFETY AND PROOF OF CONCEPT. (14th November 2022) - Yeung, Jacky; Tang, Jessica; Holle, Jonas; Teo, Charles; Sughrue, Michael
Abstract: Deficits in neurological and psychocognitive function are common for patients who have undergone surgical removal of primary tumors. Repetitive Transcranial Magnetic Stimulation (rTMS) is an emerging non-invasive tool used for the treatment of neuropsychiatric disorders. We present a retrospective review of individualized, targeted rTMS in thirteen patients who presented with post-operative neurological deficits following craniotomy for tumor resection. Multiple cortical targets were selected based on the patient's neurological disorder, the networks associated with the deficit, and anomalies in the functional connectivity of the patient's brain as determined by machine-learning. TMS treatment was performed for 5 consecutive days. EuroQol quality of life (EQ-5D), functional extremity scales, and neuropsychiatric questionnaires related to the patient's deficit were assessed prior to rTMS treatment, after treatment, and during follow-up. Five patients (38.5%) had glioblastomas; four patients (30.8%) had oligodendrogliomas; two patients (15.4%) had astrocytoma; one patient (7.7%) had ganglioglioma; and one patient (7.7%) had a pineal cyst. All thirteen patients reported significantly improved quality of life after rTMS treatment (p = 0.0065) and during follow-up (p = 0.0038) as compared to baseline. For patients with functional deficits, lower extremity functional scale (LEFS) was significantly improved one week after rTMS treatment (p = 0.0205). Upper extremity function scale (UEFS) showed non-significant trend in improvement after rTMS treatment (p = 0.0777). In the two patients who developed post-craniotomy depression, they showed a 26% and 88% reduction in depressive symptoms based on the Beck's Depression Inventory (BDI) at two-month follow-up. These results suggest that the personalized, functional connectivity approach to rTMS target and treatment may be effective for patients with post-craniotomy functional impairments and neuropsychiatric disorders. This method of post-operative interventional neuro-rehabilitation is safe, noninvasive, and allows for the simultaneous treatment of multiple symptoms.